2013
DOI: 10.4236/health.2013.57a3002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-self efficacy predicts adverse outcomes in coronary artery disease (CAD) patients

Abstract: Background: Little is known about the predictive role of Cardiac Self Efficacy (CSE) in the ensuing months following a coronary event. We sought to determine whether CSE predicts adverse events in the months following discharge in patients with Coronary Artery Disease (CAD). Design: Data from a prospective study of 193 patients recently hospitalized for CAD. Methods: Data were collected via participant self-report and medical records at 3-month post-discharge (baseline; T1), 6-month post-discharge (T2) and 9-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 34 publications
5
35
0
Order By: Relevance
“…Cardiac Self-efficacy (CSE) is in fact a cardiac-specific measure of one's belief regarding his/her ability to perform activities related to the symptoms and challenges of CVD (O'Neil et al, 2013). For those who suffer from CAD, self-efficacy is an efficient tool for the prediction of readmission chance (Sarkar et al, 2009;Negarandeh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac Self-efficacy (CSE) is in fact a cardiac-specific measure of one's belief regarding his/her ability to perform activities related to the symptoms and challenges of CVD (O'Neil et al, 2013). For those who suffer from CAD, self-efficacy is an efficient tool for the prediction of readmission chance (Sarkar et al, 2009;Negarandeh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac self-efficacy motivates the individuals to select a lifestyle about their cardiovascular disease via creating enthusiasm to adjust with such behaviors (14). The studies indicated that the individuals with high self-confidence actively participate in health promoting health plans (4,16).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac self-efficacy is indeed an exclusive cardiac scale about an individual's belief about his capabilities to do the activities related to CAD symptoms and challenges (1,14,17). Cardiac self-efficacy motivates the individuals to select a lifestyle about their cardiovascular disease via creating enthusiasm to adjust with such behaviors (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new approach to CR programs, therefore, should be multidimensional and take into account psychosocial factors. Such factors, including self-efficacy and family support, have been shown to be important predictors of the functional status of patients with cardiac disease (Sarkar et al, 2007;Tziallas & Tziallas, 2010;Brink et al, 2012;O'Neil et al, 2013;Shin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%